The image of the opponent of technological innovation in Galley Slave by A.Asimov: modern interpretation - A. E. Ulanova (Концепт: философия, религия, культура, 2020)
The image of Simon Ninheimer — the opponent of scientific and technological progress — is described by A. Azimov in the story «Galley Slave». It is used to develop the idea of resistance to mechanization, which is now finding increasingly supporters due to the increased influence of information and communication technologies in general and artificial intelligence and robotics in particular. The historical and conceptual foundations of neo-luddism are linked with modern trends calling for a gradual, controlled innovation. It is noticed that the ideas of the luddites have been preserved in romantic literature and transformed into neo-luddism in the 20th century. The theorists of this movement use philosophical concepts of different epochs (e.g. Socrates, J.-J. Rousseau and M. Heidegger) to confirm the legitimacy of their own status. As a result, in the 21st century more moderate areas of struggle against scientific and technological progress are actively developing under the influence of postmodernism. For example, the slow movement is growing strength, and its supporters are trying to slow down the pace of life and are calling for a thoughtful, responsible attitude towards emerging technologies. The positions underlying the slow movement are in tune with the dromology of P. Virilio and the slow philosophy of G. Fleistad. However, neo-luddism has social status of counterculture, but the situation can be changed due to the rapid and sometimes uncontrollable development of technology.